Evidence-Informed Deliberative Processes for HTA Around the Globe: Exploring the Next Frontiers of HTA and Best Practices Comment on "Use of Evidence-informed Deliberative Processes by Health Technology Assessment Agencies Around the Globe" - Gopinathan, Unni (Int J Health Policy Manag, 2020)
This comment reflects on an article by Oortwijn, Jansen, and Baltussen about the use and features of ‘evidence-informed deliberative processes’ (EDPs) among health technology assessment (HTA) agencies around the world and the need for more guidance. First, we highlight procedural aspects that are relevant across key steps of EDP, focusing on conflict of interest, the different roles of stakeholders throughout a HTA and public justification of decisions. Second, we discuss new knowledge and models needed to maximize the value of deliberative processes at the expanding frontiers of HTA, paying special attention to when HTA is applied in primary care, employed for public health interventions, and is produced through international collaboration.